The Monotype recorder. (London : The Monotype Corporation Limited, 1902)
The Monotype Recorder was a trade magazine published by the Monotype Corporation. It was published for about 70 years from 1902 – it almost ceased publication during World War Two. Beatrice Warde was a long-standing editor (www.metaltype.co.uk)
Online: http://www.metaltype.co.uk/monotype_recorder1.shtml
Engels
Tijdschriften
Keywords: typografie